The Relationship between Principal's Leadership and Teacher's Work Spirit on Learning Motivation of State High School Students in West Seram District - Lani Corinta; R. Kempa; S. Rumfot (International Journal of Education, Information Technology, and Others, 2022)
The principal's leadership provides work motivation to increase teacher work productivity and student learning outcomes. According to Mulyasa (2009: 98) the principal has at least a role and function as an Educator, Manager, Administrator, Supervisor, Leader, Innovator and Motivator (EMASLIM)." This study aims to describe (1) the leadership of public high school principals in West Seram District, (2) the work spirit of state high school teachers in West Seram District, (3) the learning motivation of public high school students in West Seram District, (4) Knowing the relationship between the principal's leadership with the work spirit of State Senior High School teachers in West Seram District, (5) the relationship of teacher work spirit with the learning motivation of State Senior High School students in West Seram District, (6) the magnitude of the relationship of principal leadership and teacher work spirit together with motivation studying state high school students in West Seram District. The method used in this research is descriptive quantitative method with the type of correlational research which aims to determine the relationship between principals' leadership, teacher's work spirit on learning motivation of state high school students in West Seram District, West Seram Regency. With a population of 75 teachers. The instrument is Linkert.data in this study were analyzed using SPSS for windows student version 18.00. The results of the descriptive study showed that the principal's leadership had a positive relationship to learning motivation with a correlation of r = 0.743 categorized as good. This means that the principal has shown good leadership as a principal. Teacher work enthusiasm has a positive relationship to learning motivation with a correlation value of r = 0.515, which is categorized as high teacher work morale if learning motivation is also high. From the results of the study, the average leadership of the principal and the work spirit of the teacher together has a positive relationship to students' learning motivation with a correlation value of r = 0.802.